Who makes community change for whom: the lived experience of civic leadership by citizens in a midwestern rural community - Kahl, Daniel W. (Kansas State University, 2012)
Community leadership development programs often strive to cultivate civic leadership as an approach that involves citizens in activities and efforts which serve the common good. This descriptive case study examines citizen perspectives of civic leadership in a rural Kansas community to better understand how citizens: 1) understand civic leadership, 2) are involved in civic leadership activities, 3) perceive their ability to participate in civic leadership, and 4) classify opportunities for civic leadership in their community over time. The community identified is a purposeful selection of a community identified as having strong civic leadership characteristics. Through individual interviews; focus group interviews; field observations; and supporting physical artifacts, this study triangulates findings to get a “picture” of citizen perspectives of their capacity for civic leadership. The study provides insight into how citizens perceive their ability to participate in the leadership of the community and to what degree they feel their participation is important and effective in bringing about change. Findings include that citizens identified civic leadership as action based in personal commitment and applied to community betterment. Avenues to engage in civic leadership include service through community organizations or local government, or by initiating action to address emerging issues. Not all citizens expressed full confidence and ability in making community change, and while several income levels demonstrated mixed results, only the lowest income study participants all expressed mixed combinations of ability and/or confidence in making community change. Case study discussion considers connections between civic leadership and community development and civic leadership activities in light of community power and community capacity building.
Keywords: Civic Leadership; Case Study; Community Field Theory; Community Power; Adult Education (0516); Educational leadership (0449); Social Research (0344)